Kontroversi Kepemimpinan Perempuan Dalam Hukum Islam - Himma, Himmatul 'Aliyah; Muhammad Fatoni; Ali Rahmatullah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Studying leadership, especially Islamic leadership is an interesting subject because good leadership will lead to a good social order. In Indonesia, where Muslims make up the majority of the population, incorporating democracy into Islamic teachings has always been a challenge. The inequality of women in social status is proof of this. Since ancient times, Islam has indeed abolished various types of segregation between humans, giving privileges to women as freedom is given to men. This is a matter of Islamic leadership because Islam has given women the same rights as men. This includes the administration of Islam because Islam has given women the privileges that were given to men and furthermore made commitments to women as provided to men, with the exception of the freedoms or commitments that Islam expects of men. In this way, we must balance the freedom and commitment of female pioneers with those of men as indicated by the passages in the Qur’an, hadith and ijma’ on human relations.